2022
DOI: 10.3866/pku.whxb202207026
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy-Rich Amorphous Copper Oxide Enables Highly Selective Electroreduction of Carbon Dioxide to Ethylene

Abstract: The ever-increasing carbon dioxide (CO2) emissions caused by excessive fossil fuel consumption induce environmental issues such as global warming. To overcome this, the electrocatalytic CO2 reduction (ECR) under ambient conditions offers an appealing approach for converting CO2 to value-added chemicals and realizing a closed carbon loop. Among the ECR products, ethylene (C2H4), an important building block for plastics and other chemicals, has attracted considerable attention owing to its compatibility with exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Existing laboratory methods for preparing MNCs are hard to be used for large-scale production, and the stability of the catalysts is also limited to the experimental scale. [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] Explore new catalyst design strategies and synthetic methods, especially for rapid and continuous fabrication, is needed to achieve finely controlled active sites and excellent electrocatalytic performance.…”
Section: Despite Substantial Progress Has Been Made In Research Inmentioning
confidence: 99%
“…Existing laboratory methods for preparing MNCs are hard to be used for large-scale production, and the stability of the catalysts is also limited to the experimental scale. [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] Explore new catalyst design strategies and synthetic methods, especially for rapid and continuous fabrication, is needed to achieve finely controlled active sites and excellent electrocatalytic performance.…”
Section: Despite Substantial Progress Has Been Made In Research Inmentioning
confidence: 99%
“…The cycling stability is an important criterion for judging the feasibility of BiCoO-NA/NF for practical applications. 34 As depicted in Fig. 3f, ten consecutive cycling tests at 1.3 V vs. RHE were conducted, in which the results showed that the obtained FE and conversion of BiCoO-NA/NF towards HMF oxidation can be largely maintained.…”
mentioning
confidence: 92%
“…[1][2][3][4][5] Indeed, some transition metal-based materials have been proven to activate oxygen reduction comparable to the commercial Pt/C for the AEMFC cathode. [6][7][8][9] But, for the AEMFC anode, it should be noted that the hydrogen oxidation reaction (HOR) kinetic rate of Pt in alkaline media is about two to three orders of magnitude slower than that in acidic electrolyte, 10-12 which consequently requires much higher Pt loading. 13,14 Therefore, it is imperative to design Pt-free and efficient HOR catalysts under alkaline conditions to realize the implementation of AEMFCs.Since then, various strategies have emerged to develop highperformance HOR catalysts, such as engineering the crystalline phase, 14 tuning the composition of alloy particles, 15,16 designing a core-shell structure, 17-22 constructing a hierarchical structure, 23 and so on.…”
mentioning
confidence: 99%
“…1–5 Indeed, some transition metal-based materials have been proven to activate oxygen reduction comparable to the commercial Pt/C for the AEMFC cathode. 6–9 But, for the AEMFC anode, it should be noted that the hydrogen oxidation reaction (HOR) kinetic rate of Pt in alkaline media is about two to three orders of magnitude slower than that in acidic electrolyte, 10–12 which consequently requires much higher Pt loading. 13,14 Therefore, it is imperative to design Pt-free and efficient HOR catalysts under alkaline conditions to realize the implementation of AEMFCs.…”
mentioning
confidence: 99%